ANALYSIS OF SUPPLIER AND DISTRIBUTOR SELECTION THEORIES OF STAPLE IN INDUSTRY (CASE STUDY: TOKO POJOK JAYA MALANG) - Dewi Purnamasari Salim; Wenny Gilliany; Liem Gai Sin (Journal of International Conference Proceedings (JICP), 2018)
The purpose of this research was to obtain a model of the supplier and distributor selection method in retail management. This research is important as not many study in Indonesia has been done especially for small and big retail business. This study contains of supply chain management system at the Toko Pojok Jaya with the data collection which is carried out by using the data collection done by interview method and analyzed by qualitative descriptive technique, to find model of the best supplier and distributor selection system for retail business. Keywords: distributor, retail management, supplier, Toko Pojok Jaya, qualitative descriptive, supply chain management